2022
DOI: 10.3346/jkms.2022.37.e297
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Outcomes in Pregnant Women With Coronavirus Disease 2019 in Korea

Abstract: Background This study aimed to describe the maternal, obstetrical, and neonatal outcomes in pregnant women with coronavirus disease 2019 (COVID-19) and identify the predictors associated with the severity of COVID-19. Methods This multicenter observational study included consecutive pregnant women admitted because of COVID-19 confirmed using reverse transcriptase-polymerase chain reaction (RT-PCR) test at 15 hospitals in the Republic of Korea between January 2020 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…According to a recent study of pregnant women infected with COVID-19 at 15 hospitals located in the Republic of Korea between January 2020 and December 2021, the ICU admission rate was 3.5% (9/257 people) [ 15 ], which was similar to the proportion of critically severe cases confirmed in the present study. In Korea, the rate of critically severe cases among all ages was 2.98% before the predominance of the Delta variant and 2.14% during the Delta-predominant period.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…According to a recent study of pregnant women infected with COVID-19 at 15 hospitals located in the Republic of Korea between January 2020 and December 2021, the ICU admission rate was 3.5% (9/257 people) [ 15 ], which was similar to the proportion of critically severe cases confirmed in the present study. In Korea, the rate of critically severe cases among all ages was 2.98% before the predominance of the Delta variant and 2.14% during the Delta-predominant period.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding risk factors based on the stage of pregnancy, a study found that SARS-CoV-2 infection in the second and third trimesters may lead to abnormal circulation, placental infection, and negative perinatal outcomes [ 21 ]. The risk of critically severe disease was reported to be high in patients diagnosed after 21.5 weeks of pregnancy [ 15 ]. As pregnant women diagnosed with COVID-19 in the second or third trimester are at high risk of developing critically severe symptoms, it is necessary to implement careful prevention, promotion, and treatment interventions for pregnant women diagnosed with COVID-19 in the second trimester or beyond.…”
Section: Discussionmentioning
confidence: 99%
“… 35 36 Previous study in South Korea also revealed that the gestational age of pregnant women was the risk factor for disease severity, especially if infection after 21.5 weeks (late second trimester). 37 …”
Section: Discussionmentioning
confidence: 99%
“… 64 In the Republic of Korea, the prevalence of preterm birth was 38.5% among pregnant women infected with COVID-19. 65 The long-term inter-generational effects of the COVID-19 pandemic on NCDs are of concerns and need to be monitored in the future.…”
Section: Lessons Learned From the Covid-19 Pandemic And Future Policy...mentioning
confidence: 99%